Implementation of Sharia-Based BUMDes on Economic Development and Growth in Kalatiri Village, Burau District - Selvi Selvi; Saiful Anwar (Yayasan Adra Karima Hubbi, 2024)
The aim of the research is the implementation of Sharia-based BUMDes in Kalatiri Village, Burau District, East Luwu Regency. Want to review and change the conventional system into a Sharia-based BUMDes system. And the public gets certainty of course about the contracts that will be made regarding savings and loans. The obstacles faced are the lack of public knowledge regarding financial language, financial reporting uses manual calculations. SThe solution that will be carried out in this activity is to use the method used in solving problems, namely the survey method and direct application of murabahah contracts and mudharabah contracts to solve existing problems which are then continued with research. After that, an evaluation was carried out to determine the level of success achieved by sharia-based BUMDes by reviewing understanding of Financial Reports, Islamic Economic Contracts, as well as the growth and development of BUMDes businesses.